Developing of algorithmic thinking: the base of programming. (6th September 2005) - Milkova, Eva
At the faculties preparing students in the area of computer science, the creation of algorithms forms an inseparable part of the students' basic skills. Students must be able to think algorithmically, to create various algorithms, solving given problems, starting with easy ones and consecutively increasing their algorithmic knowledge and shifts during studies, to the level where they deeply understand much more complex algorithms. Several years ago, secondary-school-students were taught how to create basic algorithms and write them into a program language, e.g., Basic or Pascal. But recently the situation in our country has changed rapidly. The user's approach by students has been increasing, but the algorithmic approach is almost unknown to them. This was the reason why our faculty decided to change the curricula with regard to accepted students who have been coming to the faculty without any previous algorithmic knowledge. In the paper, we introduce our approach to the development of the students' algorithmic thinking.